PENELUSURAN POTENSI FASXIATOR SEBAGAI ANTIKOAGULAN ALTERNATIF YANG MENCEGAH TROMBOSIS MELALUI INHIBISI SISTEM AKTIVASI KONTAK: Terobosan Penggunaan Racun Ular dalam Mengencerkan Darah yang Terkoagulasi secara Patologis - Nadine Aurelie (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2022)
Thrombosis, an imbalanced interaction between blood components, contributes greatly to deaths that occur worldwide. Therefore, treatment that can reverse the condition of blood clotting and hypercoagulability is essential. However, the drugs used to treat thrombosis-based diseases have side effects that can be seen in short and long term, particularly an increased risk of bleeding. Therefore, an alternative treatment is needed to overcome the problem of thrombosis without causing significant side effects that can endanger the lives of anticoagulant drug users. The solution to this problem is none other than nature provided, a protease inhibitor obtained through the venom of the Bungarus fasciatus snake, Fasxiator. Fasxiator can dilute blood through the inhibition of Contact Activation System (CAS) mechanism, specifically inhibiting factor XIa. The advantage of blood clotting inhibition through the CAS method is that it does not affect normal hemostasis, thereby minimizing the bleeding problems that are common with other anticoagulant drugs. Animal studies in rats demonstrated properties of high target selectivity for factor XIa, effectiveness, and high safety profile of Fasxiator, enabling the application of Fasxiator as an anticoagulant in the future. Therefore, based on the discussion that has been explained above, Fasxiator has the potential to be used as an anticoagulant on humans in the future due to its high selectivity, effectivity, and safety in previous animal studies.